CafeClima: Grow Smarter Coffee - Schmidt, Paul Gunter; Gautron, Romain Claude Gaby; Rahn, Eric Thomas; Castro Llanos, Fabio Alexander; Barrera, Santos; Delgado Muñoz, Luis Fernando; Berny Mier y Teran, Jorge C; Maina, Catherine; Umaña, Emilia; Neuschwander, Hanna; Bunn, Christian (2025)
EN: Navigating the challenges of a changing climate is critical for the future of coffee farming. CafeClima is a user-friendly web tool designed for coffee field technicians, extensionists, and others making decisions about which coffee varieties to plant. Our platform integrates the latest climate projections with real-world, global coffee variety trial results, empowering decision-makers to provide data-driven recommendations to farmers. Choosing which coffee varieties to grow is a crucial long-term decision, with consequences for yields, quality, and resilience to pests and diseases and climate shocks. Historically, access to information about variety performance under different conditions has been limited. CafeClima changes that by bringing urgently needed insights to your fingertips.